Growth on Sodium Dodecyl Sulphate (SDS) by a Bacterial Consortium Isolated from Volcanic Soil (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
During biodegradation, microorganisms can directly metabolize surfactants for energy and nutrients or co-metabolize them with other compounds. Maximum growth of the bacterial consortium on SDS was seen between 30 and 35 °C, while the optimal pH range for bacterial consortium growth was between 6.5 and 7.5. As for the nitrogen source, 2 g/L of ammonium sulfate was optimum in supporting the growth of SDS. The greatest growth rate of the bacterial consortium was recorded at a concentration of between 1 and 1.5 g/L of SDS (p
Keywords: Sodium Dodecyl Sulfate; SDS-degrading; Bacterial consortium; Mathematical model; Haldane